An empirical research: the relationship between family functioning and early adolescent's emotional intelligence - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
The aim of the present paper was to survey the relationship between family functioning and the early adolescent’s emotional intelligence. Hence, this research follows a specific objective for determination of the relationship between family functioning and early adolescent’s emotional intelligence (EQ). EQ is a set of abilities such as conception, emotion appraisal and expression, emotion management and regulation, and emotion utilization of emotion. The present study was carried out among 234 Iranian students in the second and grades of guidance schools with ages 12-15 years old. The students (girls and boys) were clustered through random and multistage sampling. Data were collected using the Schutte’s (1998) Emotional Intelligence Scale and Family Assessment Device (FAD), based on McMaster’s model. Pearson correlation between subscales of total family functioning and emotional intelligence was statistically significant. Results of the regression analysis, together with independent variables entered, indicate that as a group, the independent variables significantly contributed to the prediction of emotional intelligence.